Mesenchymal stem cells and their exosomes mitigate osteoarthritis by restoring the balance between proinflammatory Teffs and Tregs - Liu, Tianhao; Ran, Chunxiao; Zhao, Dewei; Yang, Fan; Guo, Qiang; Yang, Jiahui; Zhang, Xiuzhi (Frontiers in Aging, 2024)
Osteoarthritis (OA) is a degenerative joint disease caused by chronic inflammation that damages articular cartilage. In addition to the wear and tear of joints, aberrant remodelling driven by a significant presence of inflammatory mediators within the joint is one of the key mechanisms in the pathogenesis of OA. Among these factors, hyperactivation of Teffs subsets plays a crucial role in promoting this pathological process. The immune imbalance between proinflammatory CD4+ effector T cells (proinflammatory Teffs) and Tregs could be a crucial factor in the pathogenesis of OA. Therefore, correcting the imbalance of Tregs/proinflammatory Teffs may slow or inhibit the occurrence and development of OA, which could be a potential target for the treatment of OA. Mesenchymal stem cells (MSCs) possess anti-inflammatory and immunomodulatory properties, regulating both adaptive and innate immunity through mechanisms involving soluble factors such as IDO, PGE2, and TGF-β, as well as cell-to-cell contact and exosomes. Correcting the imbalance between Tregs and proinflammatory Teffs may be one of the mechanisms of MSCs in the treatment of OA. Therefore, this review aims to summarize the relationship between OA and the immune imbalance between Tregs and proinflammatory Teffs, the immunoregulatory role of Tregs in OA, and the role of MSCs and their exosomes in correcting the imbalance between Tregs and proinflammatory Teffs.